2004
DOI: 10.1212/01.wnl.0000129912.56486.2b
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in patients with cancer

Abstract: Embolic strokes are the commonest cause of stroke in patients with cancer, due partially to hypercoagulability, whereas atherosclerosis accounted for only 22% of stroke in this population. Outcome was primarily determined by the underlying malignancy and the patient's neurologic condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
256
4
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(282 citation statements)
references
References 35 publications
15
256
4
7
Order By: Relevance
“…In a narrow sense, TS was considered to induce strokes due to hypercoagulability, and to have a poor prognosis (8). It has been reported that patients with lung, prostate, breast or ovarian carcinoma, or malignant hematological diseases, tend to suffer from cerebral infarction more frequently compared with patients with other malignant diseases (9).…”
Section: Discussionmentioning
confidence: 99%
“…In a narrow sense, TS was considered to induce strokes due to hypercoagulability, and to have a poor prognosis (8). It has been reported that patients with lung, prostate, breast or ovarian carcinoma, or malignant hematological diseases, tend to suffer from cerebral infarction more frequently compared with patients with other malignant diseases (9).…”
Section: Discussionmentioning
confidence: 99%
“…En studie av 96 kreftpasienter med verifisert hjerneinfarkt viste at lungekreft var den dominerende krefttypen (30 %), etterfulgt av primaer hjernekreft (9 %) og prostatakreft (9 %) (6). Pasientene hadde en median overlevelsestid på 4,5 måneder etter hjerneinfarktet (6).…”
Section: Diskusjonunclassified
“…Pasientene hadde en median overlevelsestid på 4,5 måneder etter hjerneinfarktet (6). En prospektiv studie av 842 pasienter med dyp venetrombose behandlet med antikoagulasjon (lavmolekylaert heparin etterfulgt av warfarin) inkluderte 181 individer med kjent kreftsykdom.…”
Section: Diskusjonunclassified
“…Las causas del infarto cerebral son las mismas que en los pacientes sin cáncer pero se añaden algunos factores específi-cos asociados al cáncer como el estado de hipercoagulabilidad y el tratamiento, ya que tanto la quimioterapia como la radioterapia pueden predisponer a trombosis arteriales o venosas (16) . Dentro de los tratamientos específicos podemos destacar por su importante aumento del riesgo el tamoxifeno (17) , utilizado en el cáncer de mama hormono sensible, y los antiangiogénicos, como el bevacizumab (18) .…”
Section: Accidentes Cerebrovascularesunclassified